Simulasi Cfd Ang Storage Dengan Metana Sebagai Adsorbat Dan Karbon Aktif Sebagai Adsorbennya (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Increased air pollution and fuel price volatility to the attention of the world that began to study alternative energy sources. Natural gas is an alternative that can replace fuel, natural gas used was methane. There are 3 natural gas storage process LNG, CNG and ANG. LNG requires extremely low temperatures to liquefy the methane gas whereas CNG requires a very high pressure of 200 bar for storing methane, both of these processes require a very expensive cost, whereas ANG only requires a pressure of 4 bar for storing methane so that ANG is an excellent alternative possible. ANG process has been studied experimentally, while the simulation is still very rare. This study uses the simulation computational fluid dynamics (CFD) for the ANG. This modeling using Fluent. From this simulation can be obtained the distribution of temperature, pressure, adsorption capacity and adsorption rate of capacity during the adsorption process occurs. The study was conducted at a pressure of 30 bar and a temperature of 300 K, in order to obtain the result of pressure and temperature distribution are influenced by the UDF equation source terms and methane gas adsorption capacity at the time of 54000 seconds is 0.069797 kg/kg, and the rate of adsorption at the time of 54000 seconds is 5.1x10-9kg/kg.s. Keywords: Simulasi, CFD, Fluent, Adsorpsi, ANG, Karbon aktif